The Effectiveness of Dengue Vector Control : A Meta-Review - SH, Lim; Sam Froze, Jiee (John Wiley & Sons Ltd., 2025)
Background: Dengue vector control plays an important role in reducing the burden of dengue infection. This study aimed to summarise the evidence of published systematic reviews on the efficacy of dengue vector control interventions. Methods: Systematic reviews of cluster randomised controlled trials and randomised controlled trials in opulations/people exposed to the risk of dengue infection in the presence of the vector were included. All dengue vector control, all comparators and any outcomes were considered in this review. Electronic databases and reference lists were searched. Screening, full-text reviews, data extractions and quality assessments were conducted independently by two reviewers with resolution by a third reviewer. Results: A total of 15 systematic reviews were included in this study, but narrative synthesis was performed for only 3 reviews that reviewed cluster randomised controlled trials or randomised controlled trials. Community mobilisation and insecticide-treated materials were weakly effective interventions reported by two systematic reviews that have acceptable methodological quality. However, the non-overlapping of randomised controlled trials and cluster randomised controlled trials included in their respective reviews may affect the findings. Conclusion: There is insufficient evidence to recommend a method of dengue vector control management. Novel dengue vector control methods are highly encouraged for urgent trials. Until then, the current respective local governments' vector control management may still play a vital role in controlling the mosquito's propagation and transmission of dengue infection.